PENERAPAN PERMAINAN CONGKLAK UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP BILANGAN PADA ANAK KELOMPOK B1 RA TARBIYATUS SHIBYAN KUCUR DAU KABUPATEN MALANG - Riyadu Sholikhah; Khoirul Asfiyak; Ika Anggraheni (UNISMA, 2019)
This class action research aims to improve the ability to understand number concepts through congklak games. Tarbiyatus Shibyan Kucur Dau Malang Regency with a total of 26 children consisting of 18 women and 8 men. Data collection techniques used in this study were observation, interviews and documentation of children in the learning process. This study of data analysis techniques uses qualitative analysis and quantitative analysis. The results showed an increase in the ability to understand the concept through the game congklak by 88% based on the results of the first cycle and the second cycle. From the description above, it can be concluded that the game of congklak can improve the ability to understand the concept of numbers in RA Tarbiyatus Shibyan Kucur Dau, Malang Regency.